Epitope mapping of a new anti-Tn antibody detecting gastric cancer cells. - Persson, N (2017)
Here, we introduce a novel scFv antibody, G2-D11, specific for two adjacent Tn-antigens (GalNAc- Ser/Thr) binding equally to three dimeric forms of the epitope, Ser-Thr, Thr-Thr and Thr-Ser. Compared to other anti-Tn reagents, the binding of G2-D11 is minimally influenced by the peptide structure, which indicates a high degree of carbohydrate epitope dominance and a low influence from the protein backbone. With a high affinity (K Dapp = 1.3 × 10 -8 M) and no cross-reactivity to either sialyl-Tn epitope or blood group A antigens, scFv G2-D11 is an excellent candidate for a well-defined anti-Tn-antigen reagent. Detailed immunohistochemical evaluation of tissue sections from a cohort of 80 patients with gastric carcinoma showed in all cases positive tumor cells. The observed staining was localized to the cytoplasm and in some cases to the membrane, whereas the surrounding tissue was completely negative demonstrating the usefulness of the novel Tn-antigen binding antibody.